Synopsis: Market integration in Mozambique: A non-parametric extension to the threshold model - Van Campenhout, Bjorn (International Food Policy Research Institute, 2015)
Since well-functioning markets are important for economic development, policymakers need to make sure that the right policies that promote a vibrant market system are in place. This policy note is a synthesis of a technical paper that assesses the degree of maize market integration in Mozambique using a new technique an iterative process between parametric threshold modeling and kernel smoothing that allows one to estimate transaction costs in a more flexible way